Community health service capacity in China: a survey in three municipalities. Issue 1 (1st November 2011) - Zhou, Wei; Dong, Yanmin; Lin, Xiaozhi; Lu, Wenli; Tian, Xin; Yang, Lianping; Zhang, Xinping
Abstract Rationale China is reforming its health care system. It aims to strengthen primary health care through building community health facilities and assigning a 'gate‐keeper' role to primary care providers. However, it remains unknown whether community health facilities are able to fulfil such a mission. This study evaluated the service capacity of a selected sample of community health facilities and the competency of primary care practitioners employed by those facilities. Methods Three municipalities from the east, middle and west of China were purposely selected. A questionnaire was undertaken in 45 randomly selected community health facilities in the three municipalities and 700 primary care practitioners responded to the survey. The survey investigated the capacity of the community health facilities in providing diagnostic services and the competency of the primary care providers in handling common health problems. Results The most common reasons for doctor–patient encounters were common cold and chronic diseases. The capacity of the community health facilities in providing diagnostic services was limited. Although the majority of respondents believed that they could correctly identify common symptoms, many were unable to perform some essential physical examinations. Conclusion The community health facilities are not able to fulfil their designated mission because of the limited diagnostic capacity and poor competency of the primary care practitioners. Priorities should be given to capacity building for the development of community health services in the future.